Modelowanie procesów gospodarczych w literaturze i praktyce - Nowosielski, Stanisław (Modeling Economic Processes in the Literature and in the Practice, 2009)
The article presents the essence, aims and profits of modeling economic processes. It shows its place in the procedure of processes and organization management. The article also presents the levels, stages, view perspectives, approaches, methods, techniques, principles and conventions, received in modeling economic processes. It also describes practical aspects of modeling processes.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 183-198